2010
DOI: 10.1111/j.1399-3054.2010.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of chloroplastic monodehydroascorbate reductase enhanced tolerance to temperature and methyl viologen-mediated oxidative stresses

Abstract: A tomato (Lycopersicon esculentum Mill.) monodehydroascorbate reductase gene (LeMDAR) was isolated. The LeMDAR-green fluorescence protein (GFP) fusion protein was targeted to chloroplast in Arabidopsis mesophyll protoplast. RNA and protein gel blot analyses confirmed that the sense- and antisense- LeMDAR were integrated into the tomato genome. The MDAR activities and the levels of reduced ascorbate (AsA) were markedly increased in sense transgenic lines and decreased in antisense transgenic lines compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 44 publications
(48 reference statements)
5
88
0
Order By: Relevance
“…Similar results for APX transcription were obtained by Panchuk et al (2005). In Arabidopsis, Li et al (2010a) also found minor differences in the transcripts levels of MDAHR and DAHR between young and mature leaves, as recorded in the current study as well. Thus, it could be said that different molecular mechanisms participate in controlling the transcriptional regula- tion of ASA metabolism genes in young and mature leaves.…”
Section: Asa Metabolism In Young and Mature Leavessupporting
confidence: 91%
“…Similar results for APX transcription were obtained by Panchuk et al (2005). In Arabidopsis, Li et al (2010a) also found minor differences in the transcripts levels of MDAHR and DAHR between young and mature leaves, as recorded in the current study as well. Thus, it could be said that different molecular mechanisms participate in controlling the transcriptional regula- tion of ASA metabolism genes in young and mature leaves.…”
Section: Asa Metabolism In Young and Mature Leavessupporting
confidence: 91%
“…Alternatively, given evidence showing that vtc1-1 is hypersensitive to ammonium and that VTC1 has functions in cell wall polysaccharide synthesis and protein N-glycosylation (Qin et al, 2008;Barth et al, 2010), it is possible that the modulation of CSN5B by VTC1 results in altered glycoprotein synthesis, which further affects the csn5b response to salt stress. In addition, one important role of AsA is to remove ROS, which are triggered by light and oxidative stress, in plants (Smirnoff, 2000;Li et al, 2010). Plants require many small molecules to maintain a steady redox state in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Arabidopsis MDHAR gene in tobacco confers enhanced tolerance to salt and polyethylene glycol stresses [217]. Tomato chloroplastic MDHAR overexpressed in transgenic Arabidopsis enhanced its tolerance to temperature and methyl viologen-mediated oxidative stresses [218].…”
Section: Enzymes Of Ascorbate-glutathione Cyclementioning
confidence: 99%